Features of the Graphic Image in the Novel Season of Migration to the North - Elrashid Yousif Mohamed Abbas (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
This study dealt with the features of the graphic images in the novel Season of Migration to the North by the Sudanese writer Al-Tayeb Salih, in order to reveal the writer's use of the graphic image within the structure of the text of the novel. This study relied on the analytical descriptive approach, as the researcher analyzed the graphic images in the novel, such as: simile, metaphor, metaphor, and metonymy, in addition to referring to the features and purposes of these images. This study attempted to highlight the role of the Sudanese novel in enriching literary studies alongside the Arabic novel, and from what the researcher reached: the multiplicity of graphic images in the novel and its spontaneity and spontaneity, as well as the accuracy of photography that was consistent with the atmosphere of the novel, and its contribution to the interdependence of its texts, and tight coordination. The study also revealed the writerâ€™s linguistic skill, and the depth of his experience with life that was linked to its social, political and economic context, in addition to his employment of religious and popular legacies related to peopleâ€™s lives in fictional literature.ØªÙ†Ø§ÙˆÙ„Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù…Ù„Ø§Ù…Ø Ø§Ù„ØµÙˆØ± Ø§Ù„Ø¨ÙŠØ§Ù†ÙŠØ© ÙÙŠ Ø±ÙˆØ§ÙŠØ© Ù…ÙˆØ³Ù… Ø§Ù„Ù‡Ø¬Ø±Ø© Ø¥Ù„Ù‰ Ø§Ù„Ø´Ù…Ø§Ù„ Ù„Ù„ÙƒØ§ØªØ¨ Ø§Ù„Ø³ÙˆØ¯Ø§Ù†ÙŠ Ø§Ù„Ø·ÙŠØ¨ ØµØ§Ù„ØØŒ ÙˆØ°Ù„Ùƒ Ù„Ù„ÙƒØ´ÙÂ Ø¹Ù† ØªÙˆØ¸ÙŠÙ Ø§Ù„ÙƒØ§ØªØ¨ Ù„Ù„ØµÙˆØ±Ø© Ø§Ù„Ø¨ÙŠØ§Ù†ÙŠØ© Ø¯Ø§Ø®Ù„ Ø¨Ù†ÙŠØ© Ù†Øµ Ø§Ù„Ø±ÙˆØ§ÙŠØ©.Â ÙˆÙ‚Ø¯ Ø§Ø¹ØªÙ…Ø¯Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù‰ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠØ›Ø¥Ø° Ù‚Ø§Ù… Ø§Ù„Ø¨Ø§ØØ« Ø¨ØªØÙ„ÙŠÙ„ Ø§Ù„ØµÙˆØ± Ø§Ù„Ø¨ÙŠØ§Ù†ÙŠØ© Ø§Ù„Ù…ÙˆØ¬ÙˆØ¯Ø© ÙÙŠ Ø§Ù„Ø±ÙˆØ§ÙŠØ© Ù…Ø«Ù„: Ø§Ù„ØªØ´Ø¨ÙŠÙ‡ ÙˆØ§Ù„Ù…Ø¬Ø§Ø² ÙˆØ§Ù„Ø§Ø³ØªØ¹Ø§Ø±Ø© ÙˆØ§Ù„ÙƒÙ†Ø§ÙŠØ©ØŒ Ø¨Ø¬Ø§Ù†Ø¨ Ø§Ù„Ø¥Ø´Ø§Ø±Ø© Ø¥Ù„Ù‰ Ù…Ù„Ø§Ù…Ø Ù‡Ø°Ù‡ Ø§Ù„ØµÙˆØ± ÙˆØ£ØºØ±Ø§Ø¶Ù‡Ø§. ØØ§ÙˆÙ„Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† ØªØ¨Ø±Ø² Ø¯ÙˆØ± Ø§Ù„Ø±ÙˆØ§ÙŠØ© Ø§Ù„Ø³ÙˆØ¯Ø§Ù†ÙŠØ© ÙÙŠ Ø¥Ø«Ø±Ø§Ø¡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø£Ø¯Ø¨ÙŠØ© Ø¬Ù†Ø¨Ù‹Ø§ Ø¥Ù„Ù‰ Ø¬Ù†Ø¨ Ù…Ø¹ Ø§Ù„Ø±ÙˆØ§ÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆÙ…Ù…Ø§ ØªÙˆØµÙ„ Ø¥Ù„ÙŠÙ‡ Ø§Ù„Ø¨Ø§ØØ«: ØªØ¹Ø¯Ø¯ Ø§Ù„ØµÙˆØ± Ø§Ù„Ø¨ÙŠØ§Ù†ÙŠØ© ÙÙŠ Ø§Ù„Ø±ÙˆØ§ÙŠØ© ÙˆØªÙ…ÙŠØ²Ù‡Ø§ Ø¨Ø§Ù„Ø¹ÙÙˆÙŠØ©ØŒ ÙˆØ§Ù„ØªÙ„Ù‚Ø§Ø¦ÙŠØ© ÙØ¶Ù„Ø§Ù‹ Ø¹Ù† Ø¯Ù‚Ø© Ø§Ù„ØªØµÙˆÙŠØ± Ø§Ù„Ø°ÙŠ Ø§ØªØ³Ù‚ Ù…Ø¹ Ø¬Ùˆ Ø§Ù„Ø±ÙˆØ§ÙŠØ©ØŒ ÙˆØ¥Ø³Ù‡Ø§Ù…Ù‡ ÙÙŠ ØªØ±Ø§Ø¨Ø· Ù†ØµÙˆØµÙ‡Ø§ØŒ ÙˆØ¥ØÙƒØ§Ù… ØªÙ†Ø³ÙŠÙ‚Ù‡Ø§. ÙƒÙ…Ø§ ÙƒØ´ÙØª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù† Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØ§ØªØ¨ Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ÙˆØ¹Ù…Ù‚ ØªØ¬Ø±Ø¨ØªÙ‡ Ø¨Ø§Ù„ØÙŠØ§Ø© Ø§Ù„ØªÙŠ Ø§Ø±ØªØ¨Ø·Øª Ø¨Ø³ÙŠØ§Ù‚Ù‡Ø§ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ ÙˆØ§Ù„Ø³ÙŠØ§Ø³ÙŠ ÙˆØ§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠØŒ Ø¨Ø¬Ø§Ù†Ø¨ ØªÙˆØ¸ÙŠÙÙ‡ Ù„Ù„Ù…ÙˆØ±ÙˆØ«Ø§Øª Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© ÙˆØ§Ù„Ø´Ø¹Ø¨ÙŠØ© Ø§Ù„Ù…Ø±ØªØ¨Ø·Ø© Ø¨ØÙŠØ§Ø© Ø§Ù„Ù†Ù‘ÙŽØ§Ø³ ÙÙŠ Ø§Ù„Ø£Ø¯Ø¨ Ø§Ù„Ø±ÙˆØ§Ø¦ÙŠØŒ ÙˆÙƒØ°Ù„Ùƒ Ø£Ø¨Ø§Ù†Øª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù…Ù‚ Ø§Ø±ØªØ¨Ø§Ø· Ø§Ù„ÙƒØ§ØªØ¨ Ø¨Ø¨ÙŠØ¦Ù‡ Ø§Ù„Ø±ÙŠÙÙŠØ© Ø§Ù„ØªÙŠ Ù†Ø´Ø£ ÙÙŠ Ø±Ø¨ÙˆØ¹Ù‡Ø§ØŒ Ø°Ù„Ùƒ Ø§Ù„Ø§Ø±ØªØ¨Ø§Ø· Ø§Ù„Ø°ÙŠ Ø£Ø«Ø± ÙÙŠ Ù…Ø¶Ù…ÙˆÙ† Ø§Ù„Ø±ÙˆØ§ÙŠØ© Ù…ÙˆØ¶ÙˆØ¹ Ø§Ù„Ø¨ØØ«.